KORELASI MOTIVASI BELAJAR DARING DENGAN HASIL BELAJAR SISWA KELAS V SDN 11 PONTIANAK KOTA - Theresia Devi Simanjuntak; Budiman Tampubolon; Hery Kresnadi (Universitas Tanjungpura, 2021)
AbstractThis study aims to see student motivation in thematic learning during online learning with the learning outcomes fifth grade students of Elementary School 11 Pontianak. The method used is descriptive method with the form of research studies. This study is a population study with a total of 31 students. The data technique uses indirect communication techniques and documentary study techniques. The research data collection tool was a questionnaire and the average value of report cards. The results showed that the learning motivation with Very Good category level was obtained by 14 students, Good 16 students, Enough 1 student, Less and Very Less 0 students. The average value of student report cards in Very Good category 0 students, Good 10 students Enough 19 students and less 2 students. Based on the results of statistical calculations using the formula for calculating the product moment of student learning motivation with student learning outcomes, the r count is 0.453, while the r table is 0.355 which means r count> r table or (0.453> 0.355). So the relationship between student learning motivation in thematic learning during brave learning with the learning outcomes fifth grade students of Elementary School 11 Pontianak falls into the medium category.Keywords: correlation, learning motivation and learning outcomes.